Pre-linguistic infants employ complex communicative loops to engage mothers in social exchanges and repair interaction ruptures. Issue 1 (24th January 2018) - Bourvis, Nadège; Singer, Magi; Saint Georges, Catherine; Bodeau, Nicolas; Chetouani, Mohamed; Cohen, David; Feldman, Ruth
Abstract : Language has long been identified as a powerful communicative tool among humans. Yet, pre-linguistic communication, which is common in many species, is also used by human infants prior to the acquisition of language. The potential communicational value of pre-linguistic vocal interactions between human infants and mothers has been studied in the past decades. With 120 dyads (mothers and three- or six-month-old infants), we used the classical Still Face Paradigm (SFP) in which mothers interact freely with their infants, then refrain from communication (Still Face, SF), and finally resume play. We employed innovative automated techniques to measure infant and maternal vocalization and pause, and dyadic parameters (infant response to mother, joint silence and overlap) and the emotional component of Infant Directed Speech (e-IDS) throughout the interaction. We showed that: (i) during the initial free play mothers use longer vocalizations and more e-IDS when they interact with older infants and (ii) infant boys exhibit longer vocalizations and shorter pauses than girls. (iii) During the SF and reunion phases, infants show marked and sustained changes in vocalizations but their mothers do not and (iv) mother–infant dyadic parameters increase in the reunion phase. Our quantitative results show that infants, from the age of three months, actively participate to restore the interactive loop after communicative ruptures long before vocalizations show clear linguistic meaning. Thus, auditory signals provide from early in life a channel by which infants co-create interactions, enhancing the mother–infant bond.